2022
DOI: 10.24018/ejgeo.2022.3.6.330
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Remote Sensing and GIS to the Inventory and Analysis of Factors influencing on the Development of Karst Features in the Middle Atlas, Morocco

Abstract: The development of karst features is a complex and interactive process of many factors with varying influence over time. The following main factors seem to have influenced the occurrence and development of karst features in the Middle Atlas in Morocco: Precipitations after extreme weather events depending on the precipitation pattern modified by orographic effects and exposition of the terrain towards the main rain-bearing clouds are determining surface water input and infiltration as well as the outline of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…19). Along the concentrically arranged hills surrounding this enclosed topographic depression caves and springs in the Jurassic outcrops are documented [4]. Slope failure directed towards the depression center can be detected on Google Earth images.…”
Section: B Smaller Ring Structuresmentioning
confidence: 94%
See 1 more Smart Citation
“…19). Along the concentrically arranged hills surrounding this enclosed topographic depression caves and springs in the Jurassic outcrops are documented [4]. Slope failure directed towards the depression center can be detected on Google Earth images.…”
Section: B Smaller Ring Structuresmentioning
confidence: 94%
“…Although a large amount of research has been carried out related to the geologic history and structural and tectonic inventory in Northern Morocco [1]- [3] combined evaluations of different satellite data can contribute to further additional knowledge. After previous evaluations of optical and radar satellite images and digital elevation data from northern Morocco [4] it became obvious, that there are some circular structures visible on the satellite images and on morphometric maps that were neither documented on available geologic maps, nor described in the geologic literature. The reasons for this vary according to the specific situation.…”
Section: Introductionmentioning
confidence: 99%
“…Earthquake data were integrated in order to investigate if there is a relationship between surface-near geologic/tectonic structures and earthquake occurrence. Previous studies have indicated that the position of larger ring structures related to plutons with specific geomechanical properties seems to have an influence on regional earthquake occurrence and effects, such as on the macroseismic intensities [8].…”
Section: Introductionmentioning
confidence: 99%